The comparison of the rate of apical displacement in curved root canals using Neoniti and RaCe files by cone beam CT Scan - godiny, Mostafa; Nikkerdar, Nafiseh; Hatam, Reza; Shahsavand, Leila; Khavid, Atefeh (Brazilian Dental Science, 2019)
Background and aim: There is a high prevalence of root canal transportation in the teeth with the curve. effect of root canal transportation on the success of root canal therapy of tooth is negative and there is no study about comparing RaCe and Neoniti files in root canal transportation. The aim of this study is assessment and comparing two different RaCe and Neoniti files to determine transportation error in various parts of root using CBCT assessment and comparing them with each other.Method: In this experimental study 50 extracted mandibular molar teeth selected. Teeth were divided randomly into two groups i.e. 25 teeth threated with RaCe file (first group) and 25 teeth threated with Neonitu files (second group). in this study to measurement  thickness of dentine in the scan ,before and after instrumentation at the same time we used axial images that obtain from NNT viewer 6.1.0 software .Findings: in the first group ,The mean tooth transportation  in 5 mm of apex  was 0.15 and  in the second group The mean tooth transportation  in 5 mm of apex  was 0.18 mm that there was no statistically significant difference in canal transportation  between RaCe and Neoniti files in five millimeters distant from apex area (p=0.492) and the mean transportation from 9 mm of apex was 0.14 in the second group that There was no statistically significant difference in canal transportation between two  groups (p=0.911).Conclusion: The results indicated that there was no significant difference of tooth transportation between two file systems in 3, 9, 7, 5 and 11mm from the apex and both files were safe.